A low-cost version of electro-mechanical impedance technique for damage detection in reinforced concrete structures using multiple piezo configurations. Issue 8 (August 2017) - Kaur, Naveet; Li, Lingfang; Bhalla, Suresh; Xia, Yong
The electro-mechanical impedance technique has developed rapidly during the past few decades as a reliable health monitoring component of civil structures. However, the high cost of impedance analyzer/LCR meter conventionally used for data acquisition in the electro-mechanical impedance technique restricts its wide use in real applications. This article provides a comprehensive study of exploring the low-cost electro-mechanical impedance technique for health monitoring of concrete under destructive testing using multiple piezo configurations. The experimental scheme ensures separate acquisition of both the real and the imaginary components of the electro-mechanical impedance signature for detailed analysis, a feature not available in some previous low-cost adaptations. The piezo configurations covered here for comparison are the surface-bonded piezo configuration, the embedded piezo configuration, and the metal wire piezo configuration. The repeatability of the proposed low-cost electro-mechanical impedance technique is checked and the results are compared with the traditional counterpart utilizing conventional LCR meter. The two electro-mechanical impedance approaches show similar trends of the conductance signature for all configurations. In particular, the metal wire piezo configuration can be adopted as an excellent alternative in practice for reinforced concrete structures when the direct surface bonding is not feasible. Overall, the low-cost version of the electro-mechanical impedance technique is effective to detect the presence of the damage.